Peran Dukungan Sosial Dalam Meningkatkan Kesehatan Mental Remaja di Lingkungan Sekolah - Diana Arianti; Amelia Susanti (Jurnal Ners, 2025)
While social support is recognized as having a positive impact on mental health, there is a lack of research exploring the differences in influence between support from peers, teachers, and family, and how these forms of support function across different social settings. Adolescents experience many significant changes, such as physical, cognitive, and social development, which can trigger stress and mental disorders such as anxiety and depression. Research method Cross-sectional design. The study was conducted from October 2024 to February 2025 at SMPN 12 in Padang City. Population of adolescents attending junior high school. Sampling by stratified random sampling. The sample size was 200 adolescents, Multidimensional Scale of Perceived Social Support (MSPSS) instrument. Emotional Health Scale: Using measurement tools such as the General Health Questionnaire (GHQ. Statistical test Pearson Correlation Test.The results of the study showed that most respondents (60%) had high social support, while 25% were moderate, and 15% were low. In terms of mental health, 50% of adolescents showed good mental health, 30% moderate, and 20% poor. Bivariate results using Pearson correlation test showed a significant relationship between social support and adolescent mental health. With a correlation coefficient (r) = -0.48 and p = 0.001, this relationship is moderate negative and significant, which means that the higher the social support adolescents receive, the better their mental health, and vice versa, the lower the social support, the higher the level of anxiety, stress, and depression. Keywords: Social Support, Health, Mental, Adolescents.